Three-point bending behavior of Nomex honeycomb sandwich panels: Experiment and simulation. Issue 18 (17th August 2021) - Xie, Suchao; Feng, Zhejun; Zhou, Hui; Wang, Da
Abstract: To provide sufficient data and theoretical support for the practical application of Nomex honeycomb sandwich panels, the bending behavior and energy absorption characteristics of the Nomex honeycomb sandwich panels have been analyzed. Based on experiment, theory, and simulation, the relationship between bending performance and specification parameters was clarified, and the failure map of the Nomex honeycomb sandwich panels was plotted, which can provide strong data and theoretical support for the performance prediction and parameter selection of Nomex honeycomb sandwich panels.